PENGEMBANGAN BAHAN AJAR MENGGUNAKAN MODEL RME PADA TEMA 2 (SELALU BERHEMAT ENERGI) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS 4 SD SWASTA MIS AL-HIDAYAH - Ahmad Landong; Adinda Febriany Br Sembiring; Ananda Azzahra Sp; Arum Sasri Wilujeng; Rizki Rahmadani Pohan; Septi Novita Panjaitan; Siti Hazizah Br Barus; Sri Wahyuni; Tiara Puspita Sari; Widia Amalia Arfa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to develop teaching materials using the RME model in theme 2 (Always Save Energy) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) approach to improve the critical thinking skills of 4th grade students at MIS Al-Hidayah Private Elementary School. The research method used is Research and Development (R&D). Based on the validation results, the teaching materials developed were declared valid and suitable for use. Media experts provide a